Level of awareness among students of Tanauan school of craftsmanship and home industries regarding the Tanauan community e-center. - Cornejo, Ma. Flodelyn (Ma. Flodelyn Cornejo [and] Paul Nigel Dalida Custodio, 2010)
This is a descriptive correlational study on the level of awareness among students of Tanauan School of Craftsmanship and Home Industries regarding the Tanauan Community e-Center. The objectives of the study include: to determine the socio-economic and demographic characteristics of the respondents; to know the level of awareness among the students regarding the Tanauan Community e-Center; to identify the relationship of the socio-economic variables and level of awareness; and to find out the implications of level of awareness on the effectiveness and sustainability of the Tanauan Community e-Center.